Dynamic web worker pool management for highly parallel javascript web applications - Verdú, Javier; Costa, Juan José; Pajuelo, Alex (Concurrency and computation, 2016)
Summary JavaScript web applications are improving performance mainly thanks to the inclusion of new standards by HTML5. Among others, web workers API allows multithreaded JavaScript web apps to exploit parallel processors. However, developers have difficulties to determine the minimum number of web workers that provide the highest performance. But even if developers found out this optimal number, it is a static value configured at the beginning of the execution. Because users tend to execute other applications in background, the estimated number of web workers could be non‐optimal, because it may overload or underutilize the system. In this paper, we propose a solution for highly parallel web apps to dynamically adapt the number of running web workers to the actual available resources, avoiding the hassle to estimate a static optimal number of threads. The solution consists in the inclusion of a web worker pool and a simple management algorithm in the web app. Even though there are co‐running applications, the results show our approach dynamically enables a number of web workers close to the optimal. Our proposal, which is independent of the web browser, overcomes the lack of knowledge of the underlying processor architecture as well as dynamic resources availability changes. Copyright © 2015 John Wiley & Sons, Ltd.